2017
DOI: 10.4103/ccd.ccd_524_17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three different irrigants - 17% ethylenediaminetetraacetic acid, Q-MIX, and phytic acid in smear layer removal: A comparative scanning electron microscope study

Abstract: Background:Removal of smear layer from the root canal walls is important for long-standing endodontic success.Aim:The aim of this study is to evaluate and compare smear layer removing ability among 17% ethylenediaminetetraacetic acid (EDTA), Q-MIX, and phytic acid by scanning electron microscopy (SEM).Materials and Methods:This in-vitro experimental study assessed smear layer removal using three different irrigants. Thirty single-rooted freshly extracted human permanent premolars were collected, disinfected, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…There was incomplete smear layer removal at the apical portion in group 2 and 3 which is in accordance with two studies which found that both 17% EDTA and 1% IP6 were unable to completely clean the apical portion of the root (11,26). A possible explanation for this could be a decrease in dentinal tubular density from coronal to apical direction and presence of more sclerosed dentinal tubules.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was incomplete smear layer removal at the apical portion in group 2 and 3 which is in accordance with two studies which found that both 17% EDTA and 1% IP6 were unable to completely clean the apical portion of the root (11,26). A possible explanation for this could be a decrease in dentinal tubular density from coronal to apical direction and presence of more sclerosed dentinal tubules.…”
Section: Discussionsupporting
confidence: 89%
“…Results of this study demonstrated that 1% IP6 was moderately effective in removing smear layer and was less erosive than 17% EDTA. The results differ from the findings of Nassar et al (11) but are in accordance with Jagzap et al (26) in terms of smear layer removal. In addition, when erosion was evaluated, we found conflicting results with the findings of Kalcay and Tinaz (25).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is important to point out that, despite the statistically significant difference between groups with and without EDTA, it may lack clinical relevance, since its use as a final rinse at completion of root canal preparation has been proven indispensable. It allows smear layer removal, favoring the root canal cleaning, enhancing intracanal medicament diffusion through dentine, and also promoting better root canal sealing after filling (Violich & Chandler, ; Jagzap et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that QMix removes smear layer more effectively than other irrigants whereas some results were contradictory. Thirteen studies have claimed that higher effectiveness was affected by the duration of QMix irrigation [ 23 24 25 26 27 28 29 30 31 32 33 34 35 ].…”
Section: Introductionmentioning
confidence: 99%